PENGARUH EDUKASI GIZI DENGAN MEDIA VIDEO ANIMASI TERHADAP BODY IMAGE DI SMA LABORATORIUM PERCONTOHAN UPI BANDUNG TAHUN 2020 - Balqis Rahmah Sari, (2021)
This study aims to determine the effect of nutrition education using animated video media on changes in perceptions and knowledge of body image. This true experimental design study using Wilcoxon and Mann Whitney test method in Bandung was carried out on 55 students by stratified random sampling. The samples divided into 2 groups, animated video intervention group (29) and the poster control group (26). The instruments used in this study were Figure Rating Scale, Body Shape Questionnaire, and knowledge questionnaire with intervention duration of 1 week. The results of the analysis showed that there was an effect of nutrition education after being given animated videos and posters on body image knowledge (P=0.000<0.005), but no media was more effective than other media (P>0.005). The conclusion is that there is an effect of nutrition education with animated videos and posters on knowledge of body image, but there is no more effective medium between animated videos and posters.